2002
DOI: 10.1002/ijc.10317
|View full text |Cite
|
Sign up to set email alerts
|

TCR reconstitution in Jurkat reporter cells facilitates the identification of novel tumor antigens by cDNA expression cloning

Abstract: The identification of novel tumor antigens is of extreme importance for effective immunotherapy against cancer. A major obstacle in this field is the limited life span of tumorspecific cytotoxic T lymphocytes (CTLs) in vitro. Therefore we searched for a method to isolate the tumor specificity of these CTLs, i.e., their T-cell receptors (TCRs) and transfer it to an immortalized T-cell line. For this purpose, a TCRnegative Jurkat T-cell line was equipped with a nuclear factor of activated T cells ( Key words: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
0
35
1
Order By: Relevance
“…Previous studies have reported that heterologous expression of TCR in a Jurkat-derived CD8 + NFAT-luciferase reporter T cell line (Jurkat/ MA) (Aarnoudse et al, 2002) conferred antigen-specific reactivity (Birkholz et al, 2009;Schaft et al, 2006). However, in our hands, TCRmediated luciferase expression in the Jurkat/MA cell line was consistently low, yielding signals less than 5-fold above negative controls.…”
Section: Antigen-specific Reactivity Of Jurkat Effector Cells Expresscontrasting
confidence: 68%
“…Previous studies have reported that heterologous expression of TCR in a Jurkat-derived CD8 + NFAT-luciferase reporter T cell line (Jurkat/ MA) (Aarnoudse et al, 2002) conferred antigen-specific reactivity (Birkholz et al, 2009;Schaft et al, 2006). However, in our hands, TCRmediated luciferase expression in the Jurkat/MA cell line was consistently low, yielding signals less than 5-fold above negative controls.…”
Section: Antigen-specific Reactivity Of Jurkat Effector Cells Expresscontrasting
confidence: 68%
“…The TCR-minus cell line J.RT3-T3.5 [46][47][48] was infected with lentiviral particles containing the Melan-A/MART-1 specific TCR as previously described. 27 For transduction of the Melan-A/MART-1 specific TCR, 1·10 5 J.RT3-T3.5 cells were incubated with lentiviral vector at a MOI of 10.…”
Section: J-tcr-m1 Cell Line Derivationmentioning
confidence: 99%
“…Notably, TCR-transfer on primary donor T cells offers a number of advantages compared to TCR reconstitution on Jurkat cells proposed by Aarnoudse et al [15]. First, TCRtransgenic T cells are fully functional in terms of cytokine production, permitting the use of ELISA-based screening assays with their high throughput potential, sensitivity and specificity.…”
Section: Applicability Of Tcr-transgenic T Cells For Cdna Library Scrmentioning
confidence: 99%
“…First, TCRtransgenic T cells are fully functional in terms of cytokine production, permitting the use of ELISA-based screening assays with their high throughput potential, sensitivity and specificity. Moreover, use of Jurkat cells transfected with the NFATluciferase reporter construct leads to the increased risk of false-negative results due to the high background of the assay [15]. Next, the greater sensitivity of TCR-transgenic primary T cells is evident from the fact that Jurkat cells recognized melanoma cell lines only after enhancement of the antigen amount on target cells or transduction of Jurkat cells with CD8α.…”
Section: Applicability Of Tcr-transgenic T Cells For Cdna Library Scrmentioning
confidence: 99%